Validity, reliability, and comparison of the Indonesian version of two baumann skin type indicator (BSTI) questionnaires - Irwan Saputra Batubara; Irma Bernadette S. Sitohang; Sandra Widaty; Hanny Nilasari; Aria Kekalih; Sari Chairunnisa (PLoS ONE, 2026)
Background Accurate skin type classification is essential for dermatological care and research; however, commonly used classification systems do not adequately capture the multidimensional nature of skin characteristics. The Baumann Skin Type Indicator (BSTI) was developed as a questionnaire-based tool to address this limitation, and a simplified version was introduced in 2022 to improve clinical usability. To date, no validated multidimensional skin type assessment tool is available for the Indonesian population. Objectives To evaluate the validity and reliability of the Indonesian translations of the 2006 and 2022 versions of the Baumann Skin Type Indicator (BSTI-Ina) and to assess the level of agreement between the two versions when applied to Indonesian adults. Methods A cross-sectional study was conducted using Bahasa Indonesia versions of the 2006 and 2022 BSTI questionnaires, which were distributed online to 150 adult respondents. Content and construct validity were assessed, internal consistency was evaluated using Cronbach’s alpha, and agreement between the two versions was analyzed using the intraclass correlation coefficient (ICC). Results Construct validity coefficients ranged from –0.037 to 0.751 for the 2006 BSTI-Ina and from 0.231 to 0.685 for the 2022 version. Cronbach’s alpha values were ranged from 0.613–0.718 for the 2006 version and were 0.704 for the 2022 version, indicating acceptable internal consistency. The ICC between twoversions was 0.435, indicating moderate agreement. Conclusion Both the 2006 and 2022 Indonesian versions of the BSTI demonstrate acceptable validity and reliability for skin-type classification in Indonesian adults. The shorter 2022 version may offer a more practical option for routine and research use.